2017
DOI: 10.1186/s12891-017-1890-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and knee osteoarthritis: a cross-sectional study

Abstract: BackgroundOsteoarthritis (OA) is the most prevalent chronic joint disease in China. The aim of this study was to examine the association between metabolic syndrome (MetS) and knee OA in a population-based Chinese study.MethodsData included in this analysis is from a cross-sectional study, i.e., the Xiangya Hospital Health Management Center Study. MetS was diagnosed according to the criteria defined by the Chinese Diabetes Society. Radiographic knee OA was defined as changes equivalent to Kellgren-Lawrence (K-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 48 publications
3
37
2
Order By: Relevance
“…Seven studies reported data on knee or hip osteoarthritis, but not all of the studies were adjusted for BMI or physical activity. Zhou et al [39], Xie et al [37], Engstrom et al [35], Han et al [36], and Monira Hussain et al [34] reported on knee or hip osteoarthritis adjusted for physical activity (activity level). Hussain et al [34] reported on knee osteoarthritis adjusted for BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies reported data on knee or hip osteoarthritis, but not all of the studies were adjusted for BMI or physical activity. Zhou et al [39], Xie et al [37], Engstrom et al [35], Han et al [36], and Monira Hussain et al [34] reported on knee or hip osteoarthritis adjusted for physical activity (activity level). Hussain et al [34] reported on knee osteoarthritis adjusted for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, after evaluation of the full texts, eight studies were excluded for the reason that they did not satisfy our inclusion criteria: three studies offered inadequate information [25][26][27], three studies did not offer ORs or RRs for OA or adequate information to calculate these variables [28][29][30], and two studies were removed that either did not have dyslipidemia as an exposure or did not have OA as an outcome [31,32]. Ultimately, nine available observational articles were recognized for our meta-analysis [33][34][35][36][37][38][39][40][41]. Table 1 presents the principal features of the studies included in the meta-analysis, all of which were observational studies.…”
Section: Study Selection and Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested a possible link between metabolic syndrome and OA 44e47 . A recent cross-sectional study base on Chinese population reported a positive association between metabolic syndrome and radiographic knee OA 48 . Interestingly, metabolic syndrome was associated with knee osteophytes but not with joint space narrowing.…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…In addition to the physical effects, obesity is associated with an increase in systemic metabolic inflammation, and is a risk factor of metabolic syndrome (MS) [54]. Population-based studies conducted in Japan, Nigeria, Egypt, and China have shown that the accumulation of MS components, such as hypertension, dyslipidemia, and impaired glucose tolerance, is strongly correlated with the presence of knee OA and associated advanced radiographic changes, severe pain, and increased functional impairment score [55][56][57][58]. Therefore, the connection between obesity and OA is attributed to not only mechanical loading and "wear-and-tear" at the cartilage surface, but also metabolic and inflammatory mediators, specifically degradative enzymes and adipose tissue-derived cytokines (known as adipokines) [59,60].…”
Section: Obesitymentioning
confidence: 99%